Effect of Comprehensive Nursing on Pain Relief, Comfort and Burden of Family Care of Infantile Anal Fistula - Wei Y; Wang YZ; Li Y; Liu L; Sui TT; Li Y (Journal of Multidisciplinary Healthcare, 2024)
Ying Wei,1 Yan-Zhi Wang,2 Ying Li,1 Ling Liu,1 Ting-Ting Sui,2 Yuan Li1 1Department II of Anorectal Department, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 2Department I of Anorectal Department, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of ChinaCorrespondence: Ying Wei, Department II of Anorectal Department, China-Japan Friendship Hospital, No. 2, Sakura East Street, Chaoyang District, Beijing, 100029, People’s Republic of China, Tel +86-01053236548, Email Yingwei_2023@163.comObjective: To explore the effect of comprehensive nursing on pain relief, comfort and burden of family care of infantile anal fistula.Methods: This was a randomized, double-blind, controlled clinical trial. A total of 106 cases of children with anal fistula from January 2021 to December 2021 were selected and divided into observation group and control group, there were 53 cases in each group. The control group were underwent with routine nursing intervention. The observation group were underwent with video health education, peer support, music relaxation training, physiotherapy and auricular point pressing on the basis of routine nursing therapy and other measures (comprehensive nursing). The wound healing time, comfort score, complication rate and family care burden of two groups were compared.Results: After intervention, the scores of pain degree in the observation group were significantly lower than those in the control group (4.02 ± 0.85 vs 5.89 ± 2.36, p < 0.05), and the scores of comfort degree in the observation group were higher than those in the control group (70.23 ± 5.98 vs 46.88 ± 5.23, p < 0.05). After intervention, the wound healing time of the observation group was shorter than that of the control group (3.98 ± 0.63 vs 5.77 ± 1.02, p < 0.05), and the crying times of the observation group were less than that of the control group (1.22 ± 0.26 vs 4.02 ± 0.48, p < 0.05). After intervention, the total scores of family members’ care load in the observation group were significantly lower than those in the control group (37.26 ± 4.78 vs 55.99 ± 5.02, p < 0.05).Conclusion: Comprehensive nursing can effectively promote wound healing in infantile anal fistula, reduce pain, prompt children’s comfort, reduce the number of children crying, and reduce the burden of care for children’s families.Keywords: comprehensive nursing, infantile anal fistula, comfort, complications, family care burden